Pengaruh Lama Pemanasan Terhadap Kadar Alkohol Pada Nira Siwalan (Borassus flabellifer) - siti mardiyah (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2017)
abstractNira is a raw material for the manufacture of liquid brown sugar, palm sugar, and alcoholic beverages. Among these products are the most widely used alcoholic beverage. During this siwalan juice as a beverage consumed fresh, the storage period is relatively short whice for 1-2 days. If after 3 days the beverage is consumed will have a negative impact, to reduce the alcohol content is then made warming. Based on the above background can be taken formulation of the problem "whether there was an effect on levels of alcohol prolonged heating on sap siwalan"?. The purpose of this study was to determine whether there was an effect on levels of alcohol prolonged heating on sap siwalan. This research is a kind of experimental research with the aim to determine the effect of prolonged heating of the alcohol content in the sap siwalan. The sampling technique used was random sampling, totaling 24 samples. Variable work was composed of independent variables and the dependent variable. Alcohol Examination conducted on sap siwalan by doing without heating or 0 minutes, 10 minutes, 20 minutes and 30 minutes, using a number of methods Pycnometer six replication. From these results a decrease in the average alcohol content of sap siwalan on any heating for 10 min, 20 min and 30 min, after using ANOVA statistical test obtained p = 0.000 (p <0.05) can be summed Ha Ho is rejected or accepted which means there is prolonged heating effect on levels of alcohol in the juice siwalan.Key word : Nira, Level of alcohol, prolonger heating